Aggressive Central Giant Cell Granuloma of Mandible Transformed to an Enormous Vascular Lesion - Manekar, Varsha Sunil (Journal of Orofacial Research, 2012)
Aggressive central giant cell granuloma (ACGCG) is usually found in younger patients and is painful, grows rapidly, larger overall, often causes cortical perforation, root resorption and has a tendency to recur. This article is a case report of ACGCG in mandible. A girl 12 years old had features of typical giant cell reparative granuloma in the anterior mandible. After incision biopsy, she reported after 11 months. The lesion had rapidly increased in size and vascularity to an enormous tumorlike mass with engorged vessels. The lesion was of enormous size and extensive expansion was high in vascularity. The cortices remained but thinned out and perforated despite of extensive expansion. The lesion was curetted resulting in loss of continuity of the mandible. The microvascular surgery with free fibula graft was done to reconstruct the mandible. This is report of rarest case of ACGCG with enormous increase in size and vascularity which was treated successfully and rehabilitated.